2020
DOI: 10.1002/cbic.202000478
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Engineering of a Novel Baeyer‐Villiger Monooxygenase with High Normal Regioselectivity

Abstract: Baeyer‐Villiger monooxygenases (BVMOs) are remarkable biocatalysts for the Baeyer‐Villiger oxidation of ketones to generate esters or lactones. The regioselectivity of BVMOs is essential for determining the ratio of the two regioisomeric products (“normal” and “abnormal”) when catalyzing asymmetric ketone substrates. Starting from a known normal‐preferring BVMO sequence from Pseudomonas putida KT2440 (PpBVMO), a novel BVMO from Gordonia sihwensis (GsBVMO) with higher normal regioselectivity (up to 97/3) was id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Moreover, BVMOs with high regioselectivity and catalytic activity are favorable for the production of medium-chain ω-hydroxy fatty acids from long-chain keto fatty acids. Thirteen genes potentially encoding BVMOs were selected by protein BLAST in the NCBI database using the amino acid sequence of PpBVMO as the probe [40]. They were cloned and heterologously expressed in E. coli BL21 (DE3) to screen enzymes with higher catalytic activity and normal regioselectivity, including 10-ketostearic acid among the substrates.…”
Section: C9 Bifunctional Compoundsmentioning
confidence: 99%
“…Moreover, BVMOs with high regioselectivity and catalytic activity are favorable for the production of medium-chain ω-hydroxy fatty acids from long-chain keto fatty acids. Thirteen genes potentially encoding BVMOs were selected by protein BLAST in the NCBI database using the amino acid sequence of PpBVMO as the probe [40]. They were cloned and heterologously expressed in E. coli BL21 (DE3) to screen enzymes with higher catalytic activity and normal regioselectivity, including 10-ketostearic acid among the substrates.…”
Section: C9 Bifunctional Compoundsmentioning
confidence: 99%
“…Recently, Zhang et al engineered a novel BVMO ( Gs BVMO) with high expected regioselectivity and demonstrated that long-chain aliphatic keto acids 4 transformed into medium-chain ω-hydroxy fatty acids 5 with good regioselectivity and catalytic efficiency (Scheme 2 ). 18…”
Section: Table 1 Baeyer–villiger Monooxygenases (Bvmos)...mentioning
confidence: 99%
“…17 Recently, Zhang et al engineered a novel BVMO (GsBVMO) with high expected regioselectivity and demonstrated that long-chain aliphatic keto acids 4 transformed into medium-chain -hydroxy fatty acids 5 with good regioselectivity and catalytic efficiency (Scheme 2). 18 Scheme 2 Conversion of 10-ketostearic acid (4) into 9-(nonanoyloxy)nonanoic acid (5) using the variant GsBVMO C308L (C) Use of the -amino acids to create -lactam antibiotics, alkaloids, terpenoids, and -peptides has generated significant industrial interest. Various bacterial BVMOs have been used for oxidation of linear aliphatic ketones with a -amino substituent.…”
mentioning
confidence: 99%
“…To this end, several emerging ideas for the valorization of renewable oils or free fatty acids have been recently reported . Most notably, renewable long-chain unsaturation fatty acids, including oleic acid, ricinoleic acid, linoleic acid, and γ-linoleic acid, were biorefined into esters by combinatorial use of fatty acid hydratase, alcohol dehydrogenase (ADH), and Baeyer–Villiger monooxygenase (BVMO) expressed in recombinant Escherichia coli cells. ,, These esters were simultaneously converted into bifunctional chemicals, such as ω-hydroxycarboxylic acids, α,ω-dicarboxylic acids, or ω-amino fatty acids by means of lipase or esterase, ADH, and aldehyde dehydrogenase (ALDH) or transaminase. ,, However, the resultant hydrolysates of these esters, in addition to bifunctional products, also included unifunctional coproducts ( e.g. , n -pentanol, n -octanol, n -heptanoic acid, and n -nonanoic acid) formed simultaneously and unavoidably.…”
Section: Introductionmentioning
confidence: 99%